Evaluation of the Flavor Quality of Fermented Chopped Pepper by Gas Chromatography-Mass Spectrometry, High Performance Liquid Chromatography, Electronic Nose, and Electronic Togue - LIU Yuan, YANG Peiquan, ZHAO Lingyan, DENG Fangming (Shipin Kexue, 2025)
To evaluate the flavor of fermented chopped peppers from different regions, free amino acids, organic acids, and volatile compounds were analyzed by high performance liquid chromatography (HPLC) and headspace solid phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS), and taste and odor characteristics were detected using an electronic nose (E-nose) and an electronic tongue (E-tongue). Furthermore, radar plots were drawn based on the E-nose and E-tongue data, taste activity values (TAVs) and odor activity values (OAVs) were calculated, and principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) were carried out. The results showed that the E-tongue was sensitive to the sweet and umami tastes but not to the salty, bitter, or sour tastes of fermented chopped peppers from different regions. HPLC identified a total of 24 free amino acids and 7 organic acids. The contents of sweet and umami amino acids in the samples were similar to the discrimination results of E-tongue sweet and umami taste sensors. The E-nose was sensitive to alcohols, aldehydes, phenols, and nitrogen-sulfur compounds in fermented chopped peppers from different regions, showing significant differences in the types and contents of alcohols and aldehydes among the samples. GC-MS analysis identified a total of 69 volatile compounds. Combining OAV and OPLS-DA differences were found in the key aroma components of fermented chopped peppers from different regions, and the OPLS-DA results were consistent with the PCA results of E-nose. These results indicated that the combination of GC-MS, HPLC, E-nose, and E-tongue can effectively evaluate the flavor quality of fermented chopped peppers from different regions, thereby providing technical support for the quality control and enhancement of fermented chopped pepper products.